Impact of audit quality on audit fees pre and post financial crises - Bhawan, Suraj Vijaykumar (2013)
From the 1980’s research in audit service market has grown considerably. In line with that policymakers and regulators have been concerned about the role and value of external auditors and their independence. Using a sample of UK’s large companies over the period of 2006-2011 this study investigates the impact of audit quality on audit fees, whereby the proxy of audit quality is the model proposed by Ball and Shivakumar (2006). The objective was to compare the impact of audit quality on audit fees between the pre-financial crises period, which was classified as 2006-2008, and the post-financial crises period, which was classified as 2009-2011. Consistent with previous research this study found mixed results, in the pre-financial crises period the audit quality was a significant variable in explaining variations in audit fees however in the post financial period it failed to explain variations in audit fees. The by-product of the study was providing additional evidence on the determinants of audit fees. Size of auditee, size of auditor and low-balling have been found to be significant variables in explaining audit fees. In carrying out the study attention was given to the regression method used as the data format was panel. Pooled, fixed effects and random effects were all considered before drawing any conclusions from the analysis.